Single Center Retrospective Analysis of Cost and Payments for Lymphatic Surgery. Issue 6 (June 2021) - Tom, Alan R.; Boudiab, Elizabeth; Issa, Christopher; Huynh, Kristine; Lu, Stephen; Powers, Jeremy M.; Chaiyasate, Kongkrit
Abstract : Background: Insurance coverage for microsurgical lymphatic surgery continues to be sporadic, as the procedures continue to be labeled investigational. The objective of this study was to examine the typical payment patterns of our clinical practice for microsurgical lymphatic procedures. Methods: We performed a single center, single surgeon retrospective case review for all lymphovenous bypass and vascularized lymph node transfer cases preformed from 2018 to 2020. We then queried the available financial data and calculated total charges, total paid by insurance, total variable cost (cost to the hospital), and the contribution margin (difference between the amount paid and variable cost). Descriptive statistics were then collected for each subgroup for analysis. Results: Financial data were collected on 22 patients with 10 left-sided, 11 right-sided and one bilateral procedure performed. Seven procedures were done prophylactically, and 15 were done for existing lymphedema. An estimated 10 of 22 patients (45%) had Medicare, Medicaid, or Tricare, with the remaining having private insurance. We calculated an average cost of 48, 516.73, with average payment of 10, 818.68, average variable cost of 5, 567.10, for a contribution margin of +5251.58. Conclusions: Lymphedema remains a common complication of surgery and a significant cost burden to patients and the healthcare system. Microsurgical procedures offer several advantages over medical therapy. In our practice, we were routinely reimbursed for both prophylactic and therapeutic procedures with positive contribution margins for the hospital and ratios similar to other surgeries. Despite the limitations of a small retrospective review, there is no similar published cost analysis data in the current literature.